Quantitative and Qualitative Response of Fodder Maize to Use of Bulk and Nano-fertilizers in North Western Plains of India - Suryakanta Kashyap; Rakesh Kumar; Hardev Ram; Ashwani Kumar; Nirmalendu Basak; Parvender Sheoran; Subhradip Bhatacharjee; Bisworanjita Biswal; Ghous Ali; Birendra Kumar; Kanika Bhakuni; Phool Singh Hindoriya; et al. (Agronomy, 2023)
Optimizing nutrient management strategies is crucial for enhancing the growth, yield, and nutritional quality of fodder maize (Zea mays) while minimizing environmental impacts. This study investigated the effects of innovative nitrogen (N) and zinc (Zn) management approaches on fodder maize production. Different combinations of nitrogen fertilizers, including conventional urea and nano-urea, were applied in conjunction with targeted foliar sprays of zinc sulfate (ZnSO4) and nano-zinc. The experiment was carried out in a Factorial Randomized Block design with four nitrogen management strategies (control N, 100% recommended nitrogen dose RDN through urea, 50% RDN through urea + two sprays of nano-urea at six and ten leaves stages, and 33.33% RDN through urea + two sprays of nano-urea at six and ten leaves stage) and four zinc management strategies (control Zn, soil application of ZnSO4, foliar application of ZnSO4, and foliar application of nano-Zn) which were replicated thrice. The study revealed that applying 50% of RDN through urea, along with dual foliar sprays of nano-urea, achieved comparable productivity to the 100% RDN through urea only. Among the Zn managements, both foliar and soil applications of conventional ZnSO4 recorded similar green and dry fodder yields, although foliar application of ZnSO4 was observed to be superior in terms of qualitative attributes. Maize subjected to the integrated nitrogen and zinc management strategy exhibited elevated protein content and reduced fiber fractions. These findings highlight the potential of nano-urea and foliar zinc application in enhancing both productivity and nutritional quality, while reducing dependence on conventional chemical fertilizers.